Nutcracker syndrome: A novel endovascular anchoring technique for left renal vein stenting - Iman Bayat, FRACS (Vasc); Mei Ping Melody Koo, MBBS, MSurg; David Goh, FRACS (Vasc) (Journal of Vascular Surgery Cases and Innovative Techniques)
Nutcracker syndrome (NCS) is characterized by compression of the left renal vein (LRV), leading to symptoms such as left flank pain, hematuria, and pelvic congestion. Although endovascular stenting of the LRV offers a minimally invasive treatment alternative to open surgery, stent migration remains a significant risk with potentially severe complications. We present a novel, purely endovascular technique to mitigate this risk by anchoring the LRV stent using an ovarian vein stent. A 36-year-old woman presented with disabling left flank pain and pelvic discomfort unresponsive to conservative management. Clinical evaluation and imaging studies revealed significant compression of the LRV between the aorta and superior mesenteric artery, along with dilated left ovarian vein with collateral flow, consistent with NCS and pelvic venous disorder. The patient underwent endovascular stenting of the LRV using a self-expanding stent. To prevent stent migration, an additional stent was deployed into the left ovarian vein through the interstices of the LRV stent, creating an interlocking configuration for enhanced mechanical stability. Coil embolization of the ovarian vein was performed to address pelvic congestion. Postoperatively, the patient had an uncomplicated recovery and reported complete resolution of flank pain at the 1-month follow-up. Imaging confirmed proper stent positioning without migration or thrombosis. Anchoring the LRV stent using an ovarian vein stent is a feasible and effective purely endovascular strategy to prevent stent migration in patients with NCS. By enhancing stent stability without the need for surgical intervention and providing rapid symptom relief, this approach has the potential to lower patient morbidity and improve clinical outcomes. Further studies are warranted to validate the long-term efficacy and safety of this innovative technique.